IMPLEMENTASI PERATURAN DAERAH KABUPATEN AGAM NOMOR 1 TAHUN 2020 TENTANG KETENTRAMAN DAN KETERTIBAN UMUM TERHADAP PENYELENGGARAAN ORGEN TUNGGAL DI KECAMATAN TANJUNG MUTIARA - Rendra Prima Yoga; Dessy Artina; Zulwisman Zulwisman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
The implementation of a orgen tunggal often causes unrest in the community because the sound produced by a orgen tunggal sound system exceeds the average safe sound. The Agam Regency Government issued Agam Regency Regional Regulation Number 1 of 2020 concerning Public Peace and Order. However, after the enactment of the regional regulation, there are still many violations that occur in the administration of a orgen tunggal in Tanjung Mutiara District. The research objectives of this thesis are, firstly, to find out the implementation of the Agam Regency Regional Regulation Number 1 of 2020 concerning Public Peace and Order on the implementation of a orgen tunggal in Tanjung Mutiara District. Second, to find out the obstacles in the implementation of the Agam Regency Regional Regulation Number 1 of 2020 concerning Public Peace and Order on the implementation of a orgen tunggal in Tanjung Mutiara District. Third, to find out efforts to overcome obstacles in implementing the implementation of the Agam Regency Regional Regulation Number 1 of 2020 concerning Public Peace and Order on the implementation of a orgen tunggal in Tanjung Mutiara District.  This research is an empirical or sociological legal research. This research is more specific to the effectiveness of the law. The data sources used are primary data and secondary data consisting of primary legal materials, secondary legal materials, and tertiary legal materials. The data collection techniques in this study were observation, interviews, literature review, and questionnaires after the data was collected and then analyzed to draw conclusions.  From the results of the study, it was concluded that, First, the implementation of the Agam Regency Regional Regulation Number 1 of 2020 concerning Public Order and Peace on the implementation of a orgen tunggal in Tanjung Mutiara District has not gone well. Second, the obstacles in the implementation of the Agam District Regulation Number 1 of 2020 concerning Public Peace and Order on the implementation of a orgen tunggal in Tanjung Mutiara District, namely the area and human resources, budget and socialization, the substance of regional regulations and follow-up regulations, lack of community roles, community habits. . Third, efforts to overcome obstacles to the implementation of the Agam Regency Regional Regulation No. 1 of 2020 concerning Public Peace and Order on the implementation of a orgen tunggal in Tanjung Mutiara District, namely increasing cooperation between the Satpol PP Agam Regency and regional officials, making a night picket schedule for Satpol PP Agam Regency and more active again in carrying out operations on violations of the implementation of a orgen tunggal, socialization using video conferencing, as soon as possible issuing a regent's regulation, educating the importance of the role of the community, discussing with the Tanjung Mutiara District regional apparatus and other related parties Keywords: Implementation - Regional Regulation - Orgen Tunggal